Penerapan Standar Akuntansi Keuangan EMKM Dalam Penyusunan Laporan Keuangan Pada UMKM (Studi Kasus Industri Permen Lolipop Kecamatan Lowokwaru Kota Malang) - Amelia, Dewi; Afifudin, Afifudin; Anwar, Siti Aminah (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This research aims to analyze the application of accounting standards for Micro, Small and Medium Entities (SAK-EMKM) in presenting financial reports at Lollipop Candy Shop MSMEs in Lowokwaru sub-district. The research method uses a qualitative approach with a field study type of research while the research subjects are MSME Lollipop Shop business actors using primary data sources in the form of interviews and observations as well as secondary data sources in the form of documentation and several financial records of Lollipop Shop MSMEs as well as data analysis carried out through stages of data collection, data reduction, data presentation and conclusion drawing. The results of the research stated that Lollipop Shop MSMEs had recorded several simple financial reports including recognition, measurement, presentation and disclosure, but Lollipop Shop MSMEs in Lowokwaru District as a whole stated that they were not aware of the existence of the new financial accounting standard, namely SAK-EMKM.Keywords : Financial report, SAK EMKM, micro business